Enabling factors and teacher practices in using technology-assisted project-based learning in Tatweer schools in Jeddah, Saudi Arabia - Kamal, Abdulrahman (Kansas State University, 2012)
The purpose of this study was to investigate teacher practices of enabling factors in the implementation of technology-assisted PBL, in Tatweer schools in Jeddah, Saudi Arabia. This study also explored how the International Society for Technology in Education (ISTE) National Education Technology Standards for Teachers (NETS.T) were used in Tatweer classrooms and for what purposes technology was used to support PBL in the Tatweer schools. Using a constructivist framework, a convergent parallel mixed-methods design was used. The survey included closed and open-ended items, which was sent to 1073 male and female Tatweer teachers in 30 schools. Of the 710 responses received, 640 were valid, resulting in a 60% return rate. Factorial MANOVA results indicated that gender and school level were statistically significant at p < .05, while other teacher characteristics (degree types, educational degree, years of teaching experience, and content area), including their interaction, were not. ANOVA results indicated that gender effects on PBL practices were statistically significant on both teacher roles (F (1,403) = 17.77, partial ƞ2 = .042, p < .05) and learning environment (F (1, 403) = 10.83, partial ƞ2 = 026, p < .001). A means comparison indicated that males had better technology-assisted PBL practices on both variables. ANOVA and post hoc test results found that high schools used technology-assisted PBL better than elementary schools, and intermediate schools performed better than elementary schools. No significant difference was found between technology-assisted PBL practices in high schools and intermediate schools within the school system. Descriptive analysis results for research question two indicated that Tatweer school teacher technology uses were aligned with ISTE NETS.T, though there was very little use of technology in PBL. Though 177 units of information were found for the seven open-ended questions, little was related to the research questions, so Grounded Theory was used to find 19 overall themes. Findings indicated several casual conditions for the lack of technology-assisted PBL, including technology access, classroom design, space, and facilities, ministry/district support, and teacher preparation. Action strategies included providing needed technology, offering technology training, providing training in new instructional methods, creating a more flexible curriculum, and adopting advanced teaching methods and authentic assessment. Recommendations for Tatweer schools included a better learning environment, greater professional technology access, and school system support. Recommendations for future studies included conducting a similar study on other schools and a further examination of Grounded Theory findings.
Keywords: Project-based learning; Technology; Saudi Arabia; Tatweer School; Educational reform; International Society for Technology in Education National Educational Technology Standards; Education, Technology (0710)